(3TQM bGfhf GHf SjfGs - (3YR GdOjf eMeO Hf eMehO GdBedis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3hHYO aEf CMhL Ndb Gddg Edjg eMeO Hf eMehO GdBedi Mbb Cedg jbhd(B: (3Ydi Cf CfTO GdYdhe MGLI hCJegG ZGjI Hd CbOegG OQGjI hChdGgG QYGjI Yde GdWH s
(3BNQgG (B:s
(3hjQLh Gddg JYGdi CjVkG hgh GdYHO GdVYja eMeO Hf eMehO GdBedi CMSf Gddg YGbHJg ,Cf jchf eG cJHJg Ydjg cGajkG, hHebGUOg hGajkG , hCf jQRbg eGjJefGg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs